251 BYPASSED DONOR HEARTS: THE LONG TERM OUTCOME AFTER HEART TRANSPLANTATION. (10th December 2015) - Almeda, N. P.; Odim, J.; Laks, H.; Patel, J. K.; Hamilton, M.; Kobashigawa, J. A.
Abstract : Purpose: Severe shortage in organ donor pools limits the number of patients who are able to undergo transplantation. Acceptance of repairable hearts may expand the donor heart pool. We have had experience with bypass grafts (BPG) to donor hearts (use of recipient vein grafts, mammary arteries, radial arteries, and donor vein grafts) at the time of transplant for patients who are older and/or critically ill and cannot wait for a more standard donor organ. However, long-term outcome including graft patency is not known. Methods: We reviewed 22 heart transplant patients between 1992 and 2002 who received a donor heart that necessitated coronary artery bypass surgery (for coronary artery lesions ≥50%) at the time of transplantation. Results: The 22 patients had an average ischemic time of 225.7±66.1 minutes, were 13.6%CMV mismatched (3/22), had an average of 2.0±0.9 vessels bypassed (range of 1-4 vessels per patient), had an average age of 61.0±12.5 years at the time of transplant, were all male, received hearts of donors who were 72.7% (16/22) male with an average age of 53.0±7.8 years. One, three and five-year survival were 76.2% (16/21) and 70% (14/20), and 57.9% (11/19), respectively. 1 patient transferred, and 2 patients have not reached their 3 and/or 5 year follow-up. The causes of death (n=7) included rejection, infection, cardiac, malignancy, and other. Of 16 patients who had 1-year angiograms, only 1 patient had graft closure, with 2 BPGs occluded. Of the 10 patients who had a 5-year angiogram, 3 patients had at least one BPG occluded. BPG patency in these patients was 79% (15/19). Conclusion: The use of bypass donor hearts at the time of transplant appears to have acceptable 5-year survival with excellent 5-year bypass graft patency.